Steel foil for current collector and all-solid-state secondary battery
The use of ferritic stainless steel foils with tailored X-ray diffraction and surface roughness characteristics addresses the issue of buckling and bending in current collectors, enhancing the cycling performance of all-solid secondary batteries.
Patent Information
- Application Number
- JP2022106531
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-06-30
- Publication Date
- 2025-04-03
- Estimated Expiration
- 2042-06-30
AI Technical Summary
Current steel foils for current collectors in all-solid secondary batteries are prone to buckling or bending during high-temperature heat treatment, which can lead to reduced battery performance and cycling characteristics.
A ferritic stainless steel foil with a specific X-ray diffraction profile and surface roughness characteristics is used as the current collector, which includes a half-width Fw of the peak on the {110} plane ranging from 0.40 to 0.52° and arithmetic mean roughness (Ra1 and Ra2) between 0.03 to 0.30 μm, to minimize distortion and heat shrinkage.
The proposed steel foil design effectively suppresses buckling and bending during high-temperature processing, resulting in all-solid secondary batteries with excellent cycling characteristics and maintained capacity over multiple charge and discharge cycles.
Smart Images

Figure 0007656572000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a steel foil for a current collector used in an electrode of a battery, and an all-solid-state secondary battery using the steel foil for a current collector. [Background technology]
[0002] Up until now, batteries such as primary batteries and secondary batteries have been used as power sources for various electronic devices. In recent years, secondary batteries, such as lithium-ion batteries, have rapidly become more common due to the widespread use of small electronic devices such as home video cameras, laptops, and smartphones.
[0003] A secondary battery includes electrodes having a positive electrode and a negative electrode, and an electrolyte. Both the positive electrode and the negative electrode have an active material layer formed on a current collector. That is, the current collector is the base material of the electrode. The active material layer is a layer containing an active material. The current collector has a function of supplying a current to the active material and a function of retaining the active material.
[0004] Metal foils have been used as the substrate of the current collector of secondary batteries. Specifically, for example, in lithium ion batteries, copper foil is currently used as the negative electrode current collector and aluminum foil is currently used as the positive electrode current collector. On the other hand, secondary batteries may be expected to be used in harsher environments than before. For this reason, the substrate of the current collector is required to have higher strength and better heat resistance than copper foil or aluminum foil. For this reason, stainless steel foil, which has better strength and heat resistance than copper foil and aluminum foil, has been attracting attention as the substrate of the current collector.
[0005] Japanese Patent Laid-Open Publication No. 2003-178753 (Patent Document 1) and Japanese Patent Laid-Open Publication No. 2016-186881 (Patent Document 2) propose a technique for applying stainless steel foil to a current collector.
[0006] Patent Document 1 discloses a lithium battery in which the current collector of the positive electrode is made of ferritic stainless steel foil having a thickness of 12 μm or less. Patent Document 1 discloses that the reason for using ferritic stainless steel foil as the current collector is that ferritic stainless steel has good workability and is suitable for producing thin foils compared to austenitic stainless steels such as SUS304 and SUS316, and thus productivity can be improved.
[0007] Patent Document 2 discloses a lithium-ion battery negative electrode, the current collector of which is a stainless steel foil or Ni-plated steel sheet having a thickness of 15 μm or less. Patent Document 2 discloses that the reason for using stainless steel foil and Ni-plated steel sheet as the current collector is that they have high strength, do not lose strength even when heat-treated at about 300° C., and can retain their initial strength even after imidization and iminization treatments at high temperatures. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2003-178753 A [Patent Document 2] JP 2016-186881 A Summary of the Invention [Problem to be solved by the invention]
[0009] As proposed in the above Patent Documents 1 and 2, by using stainless steel foil as the substrate of the current collector, a high-strength current collector can be obtained with high productivity. Meanwhile, in recent years, the development of all-solid-state secondary batteries has been promoted with the aim of achieving both high energy density and safety. An all-solid-state secondary battery is a secondary battery in which a solid electrolyte is used instead of the electrolytic solution used in conventional secondary batteries, and the current collector, electrodes including an active material layer, electrolyte, etc. are all made of solids.
[0010] In an all-solid-state secondary battery, after an active material layer is formed on the surface of a current collector, the active material may be crystallized to obtain good battery characteristics. In this case, the current collector on which the active material layer is formed is subjected to a heat treatment at a high temperature, for example, about 700°C. On the other hand, when the active material is crystallized by such a heat treatment at a high temperature, the active material layer shrinks. As a result, the current collector may buckle or bend due to dimensional changes caused by thermal shrinkage of the active material layer and the current collector.
[0011] That is, in a steel foil for a current collector that is expected to be applied to an all-solid-state secondary battery, it is preferable that buckling or bending does not easily occur even when the active material layer shrinks due to heat treatment at a high temperature of, for example, about 700° C. However, the above Patent Documents 1 and 2 do not consider the possibility of buckling or bending occurring when the active material is crystallized as in an all-solid-state secondary battery.
[0012] The all-solid-state secondary battery is further used by repeatedly charging and discharging multiple times. On the other hand, in a secondary battery, the charge and discharge capacity of the battery tends to decrease by repeatedly charging and discharging multiple times. Therefore, in an all-solid-state secondary battery, it is preferable that the charge and discharge capacity of the battery can be maintained even after multiple charging and discharging. In this specification, the ability to maintain the charge and discharge capacity of a battery even after repeated charging and discharging is also referred to as having excellent cycle characteristics. In the above Patent Documents 1 and 2, the cycle characteristics of the all-solid-state secondary battery are not considered.
[0013] An object of the present disclosure is to provide a steel foil for a current collector which is unlikely to buckle or bend when subjected to a heat treatment at a high temperature sufficient to crystallize the active material after an active material layer is formed, and which enables the production of an all-solid-state secondary battery having excellent cycle characteristics, and to provide an all-solid-state secondary battery having the excellent cycle characteristics. [Means for solving the problem]
[0014] The steel foil for a current collector according to the present disclosure is The device is provided with ferritic stainless steel foil, In the ferritic stainless steel foil, in an X-ray diffraction profile using CoKα radiation, the half-value width Fw of the peak of the {110} plane is 0.40 to 0.52°, On the surface of the ferritic stainless steel foil, The arithmetic mean roughness in any direction is defined as Ra1, When the arithmetic mean roughness in the direction perpendicular to the arbitrary direction is defined as Ra2, Both the Ra1 and the Ra2 are in the range of 0.03 to 0.30 μm.
[0015] The all-solid-state secondary battery according to the present disclosure is The current collector steel foil, An active material layer; A solid electrolyte layer; and a current collector layer. Effect of the Invention
[0016] The steel foil for a current collector according to the present disclosure is resistant to buckling or bending when subjected to a heat treatment at a high temperature sufficient to crystallize the active material after the active material layer is formed, and an all-solid-state secondary battery having excellent cycle characteristics can be obtained. The all-solid-state secondary battery according to the present disclosure has excellent cycle characteristics. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] First, the inventors considered using a ferritic stainless steel foil as the substrate of the steel foil for the current collector. The ferritic stainless steel foil has higher stability at high temperatures than non-ferrous metal foils such as aluminum foil. Furthermore, the ferritic stainless steel foil has lower electrical resistance and higher electrical conductivity than austenitic stainless steel foil. From these points, the inventors decided to use a ferritic stainless steel foil as the substrate of the steel foil for the current collector.
[0018] [Buckling and bending due to heat treatment] As described above, it is preferable that a steel foil for a current collector that is expected to be applied to an all-solid-state secondary battery is less likely to buckle or bend even when the active material layer shrinks due to heat treatment at a high temperature of, for example, about 700° C. The present inventors therefore conducted detailed studies on steel foils that are less likely to buckle or bend due to heat treatment at a high temperature of about 700° C. As a result of detailed studies, the present inventors thought that if the steel foil for a current collector can also be thermally shrunk to a certain extent during the thermal shrinkage of the active material layer accompanying the crystallization of the active material, it may be possible to suppress the occurrence of buckling or bending of the steel foil for a current collector.
[0019] Specifically, the present inventors focused on the distortion of the ferritic stainless steel foil, which is the base material of the steel foil for a current collector. If the amount of distortion of the ferritic stainless steel foil can be controlled, it may be possible to control the thermal contraction of the steel foil for a current collector during heat treatment at about 700°C after forming an active material layer. As a result, it may be possible to suppress the occurrence of buckling or bending when the steel foil for a current collector on which an active material layer has been formed is heat treated at about 700°C.
[0020] As a result of detailed investigations by the inventors based on the above findings, it was found that if the half-width Fw of the peak of the {110} plane in the X-ray diffraction profile of a ferritic stainless steel foil using CoKα radiation is 0.40 to 0.52°, the occurrence of buckling or bending can be suppressed when the steel foil for a current collector on which an active material layer is formed is heat-treated at about 700°C.
[0021] If the half-width Fw of the {110} plane peak in the X-ray diffraction profile of the ferritic stainless steel foil using CoKα rays (hereinafter also simply referred to as "half-width Fw of the {110} plane") is too small, the amount of distortion of the ferritic stainless steel foil is too small. In this case, the strain is not released during heat treatment at about 700 ° C, and no thermal shrinkage occurs during heat treatment. As a result, the steel foil for the current collector is pulled by the thermal shrinkage of the active material layer and bent. On the other hand, if the half-width Fw of the {110} plane of the ferritic stainless steel foil is too large, the amount of distortion of the ferritic stainless steel foil becomes too large. In this case, the strain is released too much during heat treatment at about 700 ° C, and excessive thermal shrinkage occurs during heat treatment. As a result, the thermal shrinkage exceeds the thermal shrinkage of the active material layer, and buckling occurs in the steel foil for the current collector.
[0022] Therefore, the current collector steel foil according to this embodiment has a half-value width Fw of the peak of the {110} plane of the ferritic stainless steel foil of 0.40 to 0.52°. As a result, even if an active material layer is formed on the surface of the current collector steel foil according to this embodiment and then a heat treatment is performed at about 700° C., buckling or bending is unlikely to occur.
[0023] [Cycle characteristics] As described above, it is preferable that the all-solid-state secondary battery has excellent cycle characteristics. Therefore, the present inventors have conducted detailed studies on steel foils for current collectors to obtain all-solid-state secondary batteries having excellent cycle characteristics. Specifically, the present inventors manufactured various ferritic stainless steel foils having a half-width Fw of the {110} plane peak of 0.40 to 0.52°, and prepared simulated all-solid-state secondary batteries. The prepared simulated batteries were repeatedly charged and discharged multiple times to evaluate the retention rate of the charge and discharge capacity (capacity retention rate) of the battery. As a result, the present inventors have newly discovered that the surface roughness of the ferritic stainless steel foil affects the cycle characteristics of the all-solid-state secondary battery.
[0024] First, the inventors of the present invention have focused on the arithmetic mean roughness in two directions of the surface, taking into consideration that the surface roughness of the ferritic stainless steel foil may have anisotropy. Specifically, in this specification, the arithmetic mean roughness in any direction of the surface of the ferritic stainless steel foil is defined as Ra1, and the arithmetic mean roughness in the direction perpendicular to the direction of Ra1 is defined as Ra2. For example, when Ra1 is the arithmetic mean roughness in the rolling direction of the ferritic stainless steel foil, Ra2 is the arithmetic mean roughness in the width direction of the ferritic stainless steel foil.
[0025] As a result of detailed studies by the present inventors, it has been found that if Ra1 or Ra2 is less than 0.03 μm, the capacity retention rate of the battery gradually decreases by repeating charge and discharge, and if Ra1 or Ra2 exceeds 0.30 μm, the capacity retention rate may suddenly decrease in the process of repeating charge and discharge. That is, as a result of detailed studies by the present inventors, when a ferritic stainless steel foil having a half-width Fw of the peak of the {110} plane of 0.40 to 0.52° is used as a substrate of a steel foil for a current collector of an all-solid-state secondary battery, if both Ra1 and Ra2 satisfy 0.03 to 0.30 μm, not only buckling and bending are unlikely to occur, but also an all-solid-state secondary battery having excellent cycle characteristics can be obtained. The present inventors speculate that the reason for this is as follows.
[0026] First, when an all-solid-state secondary battery is manufactured using a steel foil for a current collector having a ferritic stainless steel foil as a base material, a thin film, typically an active material layer, is laminated on the surface of the steel foil. In addition, a vacuum film-forming method, typically a sputtering method or an electron beam deposition method, may be used to form the thin film. In an all-solid-state secondary battery, the thin film laminated on the surface of the steel foil is formed very thin and uniformly by using the vacuum film-forming method. As a result, in an all-solid-state secondary battery, the surface roughness of the ferritic stainless steel foil, which is the base material, and the surface roughness of the thin film, such as the active material layer, tend to be about the same.
[0027] In addition, in an all-solid-state secondary battery, a metal oxidation-reduction reaction occurs during charging and discharging, and some metals may react at this time. In this case, the reacted metal may grow in a dendrite shape, which may cause a short circuit in the battery. Furthermore, if the surface roughness of the ferritic stainless steel foil is too large, the surface roughness of the thin film (active material layer, electrolyte layer, etc.) laminated on the surface of the steel foil will also be large. In this case, the shape of the interface between the steel foil for the current collector and the thin film, and the interface between the thin films themselves, tends to be complicated, which tends to induce a reaction of metals and dendrite growth. In other words, the greater the surface roughness of the ferritic stainless steel foil, which is the current collector substrate, the more likely it is that a short circuit will occur during charging and discharging. The present inventors speculate that this is why a sudden decrease in capacity retention occurs during the process of repeated charging and discharging.
[0028] On the other hand, if the surface roughness of the ferritic stainless steel foil is too small, the surface roughness of the thin film laminated on the surface of the steel foil will also be small. In this case, the interface between the steel foil for the current collector and the thin film, and the interface between the thin films themselves will be too smooth. As a result, the adhesion of the thin film will decrease, and the thin film may easily peel off due to the volume expansion and contraction of the active material layer, etc., accompanying charge and discharge. The present inventors speculate that the charge and discharge capacity of the battery will gradually decrease as a result of repeated charge and discharge in this way.
[0029] The present inventors presume that, by the above mechanism, when a ferritic stainless steel foil having a half-width Fw of the {110} plane of 0.40 to 0.52° is used as a base material for a steel foil for a current collector of an all-solid-state secondary battery, by satisfying both Ra1 and Ra2 of 0.03 to 0.30 μm, buckling and bending are unlikely to occur even when a heat treatment is performed at about 700 ° C after an active material layer is formed on the surface, and an all-solid-state secondary battery having excellent cycle characteristics can be obtained. Note that, by a mechanism different from the above mechanism, a steel foil for a current collector satisfying the configuration of this embodiment is unlikely to buckle or bend even when a heat treatment is performed at about 700 ° C after an active material layer is formed on the surface, and an all-solid-state secondary battery using the steel foil for a current collector may have excellent cycle characteristics. However, when a ferritic stainless steel foil having a half-width Fw of the peak of the {110} plane of 0.40 to 0.52° is used as a base material for a steel foil for a current collector of an all-solid-state secondary battery, by satisfying both Ra1 and Ra2 of 0.03 to 0.30 μm, buckling or bending is unlikely to occur even when a heat treatment is performed at about 700° C. after forming an active material layer on the surface, and an all-solid-state secondary battery having excellent cycle characteristics can be obtained, as proven by the examples described later.
[0030] The gist of the steel foil for a current collector according to the present embodiment, which was completed based on the above findings, is as follows.
[0031] [1] A steel foil for a current collector, The device is provided with ferritic stainless steel foil, In the ferritic stainless steel foil, in an X-ray diffraction profile using CoKα radiation, the half-value width Fw of the peak of the {110} plane is 0.40 to 0.52°, On the surface of the ferritic stainless steel foil, The arithmetic mean roughness in any direction is defined as Ra1, When the arithmetic mean roughness in the direction perpendicular to the arbitrary direction is defined as Ra2, The Ra1 and the Ra2 are both 0.03 to 0.30 μm. Steel foil for current collectors.
[0032] [2] The steel foil for a current collector according to [1], The thickness of the ferritic stainless steel foil is 5 to 60 μm. Steel foil for current collectors.
[0033] [3] The steel foil for a current collector according to [1], A resin coating is formed on the surface of the ferritic stainless steel foil. Steel foil for current collectors.
[0034] [4] The steel foil for a current collector according to [2], A resin coating is formed on the surface of the ferritic stainless steel foil. Steel foil for current collectors.
[0035] [5] [1] to [4], and An active material layer; A solid electrolyte layer; A current collector layer. All-solid-state secondary battery.
[0036] Hereinafter, the steel foil for a current collector according to this embodiment will be described.
[0037] [Steel foil for current collectors] The current collector steel foil according to this embodiment includes a ferritic stainless steel foil as a substrate. The current collector steel foil according to this embodiment may include a component other than the ferritic stainless steel foil.
[0038] [Ferritic stainless steel foil] The substrate of the steel foil for a current collector according to the present embodiment is a ferritic stainless steel foil. Specifically, the ferritic stainless steel foil means a steel foil having a Cr content of 10.5% or more and a microstructure mainly composed of ferrite. In this specification, the microstructure mainly composed of ferrite means that the volume fraction of ferrite in the microstructure is 95% or more.
[0039] In this embodiment, the ferritic stainless steel foil can be a metal foil made of a well-known ferritic stainless steel. The ferritic stainless steel foil according to this embodiment may be, for example, SUS405, SUS410L, SUS429, SUS430, SUS430LX, SUS430J1L, SUS434, SUS436L, SUS436J1L, SUS443J1, SUS444, SUS445J1, SUS445J2, SUS447J1, or SUSXM27 as specified in JIS G 4305 (2012).
[0040] The ferritic stainless steel foil according to the present embodiment may be, for example, 403, 405, 409L, 410, 410L, 410S, 415, 420J1, 420J2, 420, 429, 429J1, 430, 430J1L, 430LX, 430Ti, 434, 436, 436J1L, 439, 441, 444, 445, 445J1, 445J2, 446, 447, or 448 as specified in ASTM A 280 (2006).
[0041] Preferably, the thickness of the ferritic stainless steel foil according to this embodiment is 5 to 60 μm. The thinner the ferritic stainless steel foil, the thinner the current collector steel foil. As a result, the energy density of a battery using an electrode manufactured using the current collector steel foil is increased. However, if the ferritic stainless steel foil is too thin, it becomes difficult to manufacture the current collector steel foil. Therefore, in this embodiment, the thickness of the ferritic stainless steel foil is preferably 5 to 60 μm.
[0042] [FWHM of {110} plane peak Fw] The ferritic stainless steel foil according to this embodiment has a half-value width Fw of the {110} plane peak in an X-ray diffraction profile using CoKα radiation of 0.40 to 0.52°. As a result, the current collector steel foil using the ferritic stainless steel foil according to this embodiment as a base material is less likely to buckle or bend when heat-treated at about 700° C. after an active material layer is formed.
[0043] If the half-width Fw of the {110} plane of the ferritic stainless steel foil is too small, the amount of distortion of the ferritic stainless steel foil is too small. In this case, the strain is not released during heat treatment at about 700 ° C, and no thermal shrinkage occurs during heat treatment. As a result, the steel foil for the current collector is pulled by the thermal shrinkage of the active material layer and bent. On the other hand, if the half-width Fw of the {110} plane of the ferritic stainless steel foil is too large, the amount of distortion of the ferritic stainless steel foil becomes too large. In this case, the strain is released too much during heat treatment at about 700 ° C, and excessive thermal shrinkage occurs during heat treatment. As a result, the thermal shrinkage exceeds the thermal shrinkage of the active material layer, and buckling occurs in the steel foil for the current collector.
[0044] The half-width Fw of the {110} plane of the ferritic stainless steel foil according to the present embodiment is preferably 0.41, more preferably 0.43, and even more preferably 0.45. If the half-width Fw of the {110} plane is 0.45 or more, bending can be further suppressed when the active material layer is formed and then heat-treated at about 700°C. The half-width Fw of the {110} plane of the ferritic stainless steel foil according to the present embodiment is preferably 0.51, more preferably 0.50, and even more preferably 0.48.
[0045] In this embodiment, the half-value width Fw of the {110} plane of the ferritic stainless steel foil can be measured by the following method. A test piece is prepared from the steel foil for current collector according to this embodiment. The size of the test piece is not particularly limited, and the thickness of the test piece is the same as that of the steel foil. Measurement is performed on the observation surface of the test piece by grazing incident X-ray diffraction (GIXD). Specifically, the radiation source is CoKα radiation, the tube voltage is 40 kV, and the tube current is 135 mA. The X-ray flux is collimated by a mirror. The solar slit is set to 5° on the entrance side and 2.5° on the diffraction side. The incidence angle is set to 12 conditions in the range of 1 to 25° so that the measurement depth from the observation surface of the test piece is 12 points in the range of 0.19 to 4.60 μm. At each measurement point, the peak of the {110} plane is identified and the half-value width is obtained. The arithmetic mean of the 12 half-widths obtained is defined as the half-width Fw of the {110} plane. The measurement depth is calculated by finding the X-ray penetration depth t that satisfies μt=1, where μ is the linear absorption coefficient, and converting it into the depth from the observation surface of the test piece. The mass absorption coefficient used is 19.11Cr-1.77Mo-78.38Fe (mass%). Furthermore, the density of the ferritic stainless steel foil is 7.75g / cm. 3 is used.
[0046] [Arithmetic mean roughness Ra1 and Ra2] In the ferritic stainless steel foil according to the present embodiment, when the arithmetic mean roughness in an arbitrary direction on the surface is defined as Ra1 and the arithmetic mean roughness in a direction perpendicular to the direction of Ra1 is defined as Ra2, both Ra1 and Ra2 are 0.03 to 0.30 μm. As a result, when the current collector steel foil using the ferritic stainless steel foil according to the present embodiment as a base material is applied to an all-solid-state secondary battery, excellent cycle characteristics are obtained.
[0047] When the surface of the ferritic stainless steel foil has Ra1 or Ra2 of less than 0.03 μm, the surface roughness of the thin film (active material layer, electrolyte layer, etc.) laminated on the surface of the ferritic stainless steel foil is also small. As a result, the adhesion of the thin film is reduced, and the thin film is likely to peel off due to the volume expansion and contraction of the active material layer, etc., accompanying charge and discharge, and the charge and discharge capacity of the battery may gradually decrease. On the other hand, when the surface of the ferritic stainless steel foil has Ra1 or Ra2 of more than 0.30 μm, the shape of the interface between the collector steel foil and the thin film and the interface between the thin films becomes complex, and a short circuit is likely to occur during charge and discharge. As a result, a rapid decrease in charge and discharge capacity may occur in the process of repeated charge and discharge. Therefore, the ferritic stainless steel foil according to this embodiment has Ra1 and Ra2 of 0.03 to 0.30 μm on its surface.
[0048] In addition, when Ra1 or Ra2 exceeds 0.30 μm, if the mechanism by which a short circuit is likely to occur during charging and discharging of an all-solid-state secondary battery is as described above, it is considered that a short circuit is likely to occur at a portion of the surface of the steel foil where the unevenness is locally large. Therefore, the maximum roughness Rz may be dominant among the parameters of surface roughness in the influence on the tendency of a short circuit to occur in this mechanism. However, in the ferritic stainless steel foil according to the present embodiment, a similar tendency is confirmed in the arithmetic mean roughness Ra and the maximum roughness Rz. Therefore, in the present embodiment, the arithmetic mean roughness Ra1 and Ra2 in two perpendicular directions are used as indicators of adhesion and short circuit resistance.
[0049] In the surface of the ferritic stainless steel foil according to the present embodiment, the preferred lower limit of Ra1 and Ra2 is 0.04 μm, more preferably 0.05 μm. In the surface of the ferritic stainless steel foil according to the present embodiment, the preferred upper limit of Ra1 and Ra2 is 0.29 μm, more preferably 0.28 μm.
[0050] In this embodiment, Ra1 and Ra2 on the surface of the ferritic stainless steel foil can be measured by the following method. First, a test piece is cut out from the ferritic stainless steel foil according to this embodiment and fixed to a glass substrate. Three arbitrary points are identified on the surface of the fixed test piece as measurement points. At each measurement point, an arbitrary direction is identified as "direction 1", and a direction perpendicular to direction 1 is identified as "direction 2". Preferably, direction 1 is parallel to the rolling direction of the ferritic stainless steel foil. However, even a person skilled in the art may not be able to identify the rolling direction of the ferritic stainless steel foil. In this case, the direction in which the arithmetic mean roughness is measured does not have to be parallel to the rolling direction.
[0051] At each measurement point, the arithmetic mean roughness is measured in each of directions 1 and 2 in accordance with the method specified in JIS B 0601 (2001), and defined as Ra1 (μm) and Ra2 (μm). The roughness meter used to measure the arithmetic mean roughness may be, for example, a contact type roughness meter, a surface roughness tester Surftest SJ-301 (product name) manufactured by Mitutoyo Corporation. Specifically, the conditions for calculating the roughness curve are as follows: Measuring force: 0.75mN Stylus tip shape (when using a contact type roughness gauge): 2μmR60° Cutoff value λc: 0.25 mm Cutoff value λs: 2.5μm Number of sections: 5 Measurement speed: 0.25mm / sec Reference length: 0.25 mm Evaluation length: 1.25mm
[0052] [Resin coating] The steel foil for a current collector according to this embodiment may include a resin coating formed on the surface of the ferritic stainless steel foil. By forming a resin coating on the surface of the ferritic stainless steel foil, the insulation, heat resistance, and flatness of the steel foil for a current collector can be improved. In this embodiment, the resin coating may be formed on both sides of the ferritic stainless steel foil, on one side, or not at all. Furthermore, the resin coating may be formed on a part of one side of the ferritic stainless steel foil, or on the entirety of the one side.
[0053] The resin coating is not particularly limited, and may be, for example, an inorganic-organic hybrid resin coating. The inorganic-organic hybrid resin coating refers to a resin coating formed by combining an inorganic component and an organic component. Specifically, the inorganic-organic hybrid resin coating may be a siloxane coating having an inorganic skeleton with a siloxane bond developed in a three-dimensional network structure as the main skeleton, in which at least one of the bridging oxygens in the skeleton is replaced with an organic group and / or a hydrogen atom. That is, in this embodiment, a siloxane coating in which the oxygen concentration [O] (mol / L) and the silicon concentration [Si] (mol / L) in the coating satisfy 1<[O] / [Si]<2 can be used as the resin coating.
[0054] As described above, the thinner the steel foil for a current collector, the higher the energy density of a battery using an electrode manufactured using the steel foil for a current collector. Therefore, in this embodiment, when a resin coating is formed, it is preferable that the thickness of the resin coating is thin. On the other hand, if the resin coating is too thin, the above-mentioned insulation properties, heat resistance, and flatness may not be sufficiently obtained. Therefore, in this embodiment, when a resin coating is formed, it is preferable that the thickness of the resin coating is 0.3 to 5.0 μm.
[0055] [Other configurations] The current collector steel foil according to the present embodiment may include a configuration other than the ferritic stainless steel foil and the resin coating. For example, the current collector steel foil may have a layer other than the resin coating on the surface thereof. In this case, it is preferable that the layer other than the resin coating has electrical conductivity.
[0056] [battery] As described above, the steel foil for a current collector according to this embodiment can be used as an electrode of a battery by forming an active material layer on or above the surface thereof. Here, the steel foil for a current collector according to this embodiment can be used as a steel foil for a positive electrode current collector, and can also be used as a steel foil for a negative electrode current collector. The steel foil for a current collector according to this embodiment is not limited to the battery in which it is used. The steel foil for a current collector according to this embodiment can be used as an electrode of an all-solid-state secondary battery, an electrode of a non-aqueous electrolyte secondary battery, or an electrode of an aqueous electrolyte secondary battery. Cut .
[0057] [All-solid-state secondary battery] Preferably, the battery according to the present embodiment is an all-solid-state secondary battery. When the battery according to the present embodiment is an all-solid-state secondary battery, the all-solid-state secondary battery includes the current collector steel foil according to the present embodiment, an active material layer, a solid electrolyte layer, and a current collector layer.
[0058] The all-solid-state secondary battery according to the present embodiment includes an active material layer. Here, the active material layer is not particularly limited and may be obtained by a thin film containing a known active material. When the active material layer is a positive electrode active material layer, the positive electrode active material may be, for example, lithium cobalt oxide, a ternary material, lithium manganate, lithium iron phosphate, or high nickel. When the active material layer is a negative electrode active material layer, the negative electrode active material may be, for example, a carbon-based material represented by graphite, an alloy material represented by CuSn alloy or NiTiSi alloy, or a Si-based material represented by SiO. In addition, in the all-solid-state secondary battery, there may be cases where the negative electrode active material layer is not formed. In this case, the active material layer means the positive electrode active material layer.
[0059] More specifically, when the steel foil for a current collector according to this embodiment is used in an all-solid-state lithium ion secondary battery, the positive electrode active material may be, for example, molybdenum oxide (MoO3), vanadium oxide (VO3), lithium manganese oxide (LiMn2O4), lithium cobalt oxide (LiCoO2), solid solution oxide (Li2MnO3-LiMO2 (M=Co, Ni, etc.)), lithium-manganese-nickel oxide (LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2), olivine-type lithium phosphate oxide (LiFePO4), tungsten oxide (WO3), and other composite oxides can be used.
[0060] In this embodiment, the method of forming the active material layer using the active material exemplified above is not particularly limited. For example, a vacuum film formation method such as a sputtering method or an electron beam deposition method is used as a method of forming the active material layer. Furthermore, as described above, in an all-solid-state secondary battery, the active material may be crystallized after the active material layer is formed on the surface of the current collector. In this case, after the active material layer is formed on or above the steel foil for the current collector, a heat treatment is performed at a high temperature of, for example, about 700°C. The steel foil for the current collector according to this embodiment is unlikely to buckle or bend even if a heat treatment of about 700°C is performed after the active material layer is formed.
[0061] The all-solid-state secondary battery according to the present embodiment further includes a solid electrolyte layer. The solid electrolyte layer is not particularly limited and may be obtained by a thin film containing a well-known solid electrolyte. Specifically, when the all-solid-state secondary battery according to the present embodiment is a thin-film type all-solid-state lithium ion secondary battery, the solid electrolyte may be, for example, Li7Al 0.1 La3Zr2O 12 , Li 1.3 Al 0.3 Ti 1.7 (PO4)3, (Li,La)TiO3, Li5La3Ti2O 12 ,Li 3.09 BO 2.53 N 0.52 , Li3PON4 can be used.
[0062] The all-solid-state secondary battery according to the present embodiment further includes a current collector layer. As described above, the current collector steel foil according to the present embodiment can be used as a positive current collector steel foil or as a negative current collector steel foil. When the current collector steel foil according to the present embodiment is used as a positive current collector steel foil, the current collector layer is used as a negative current collector. When the current collector steel foil according to the present embodiment is used as a negative current collector steel foil, the current collector layer is used as a positive current collector.
[0063] In this embodiment, the material used for the current collector layer may be a well-known material selected from the viewpoint of electrochemical corrosion resistance and volume resistivity at the operating potential of the positive and negative electrodes. When the current collector layer is used as a positive electrode current collector, the current collector layer may be made of, for example, platinum (Pt), gold (Au), aluminum (Al), or titanium nitride (TiN). When the current collector layer is used as a negative electrode current collector, the current collector layer may be made of, for example, platinum (Pt), gold (Au), silver (Ag), copper (Cu), nickel (Ni), or titanium nitride (TiN).
[0064] The all-solid-state secondary battery according to the present embodiment may include a configuration other than the steel foil for current collector according to the present embodiment, the active material layer, the solid electrolyte layer, and the current collector layer. For example, a conductor layer may be formed between the steel foil for current collector according to the present embodiment and the active material layer. That is, in the all-solid-state secondary battery according to the present embodiment, the conductor layer may have any configuration. When a conductor layer is formed between the steel foil for current collector and the active material layer, diffusion between the steel foil for current collector and the active material layer can be suppressed. In this case, the interface resistance between the steel foil for current collector and the active material layer can be further suppressed.
[0065] In the all-solid-state secondary battery according to the present embodiment, when forming a conductive layer, the material used for the conductive layer may be a well-known material selected from the viewpoint of electrochemical corrosion resistance and volume resistivity at the operating potential of the positive and negative electrodes. For example, platinum (Pt), gold (Au), aluminum (Al), and titanium nitride (TiN) may be used for the conductive layer on the positive electrode side. For example, platinum (Pt), gold (Au), silver (Ag), copper (Cu), nickel (Ni), and titanium nitride (TiN) may be used for the conductive layer on the negative electrode side.
[0066] The all-solid-state secondary battery according to the present embodiment may further include a configuration other than the current collector steel foil according to the present embodiment, the conductor layer, the active material layer, the solid electrolyte layer, and the current collector layer. In this case, for example, a protective layer that protects the active material layer may be included, or a case that covers the entire battery may be included. Note that, when a protective layer or a case is included, it is preferable that the protective layer or the case does not have electrical conductivity.
[0067] [Buckling] The steel foil for a current collector according to the present embodiment is resistant to buckling or bending when subjected to a heat treatment at a high temperature sufficient to crystallize the active material after the active material layer is formed. In the present embodiment, the resistance to buckling can be evaluated by the following method.
[0068] An active material layer is formed on the surface of the steel foil for current collector according to this embodiment, using lithium cobalt oxide (LiCoO2) as the active material. The size of the steel foil for current collector is, for example, 300 to 600 mm in the width direction of the steel foil. The steel foil for current collector on which the active material has been formed by the vacuum film forming method is heat-treated at 700°C for 20 minutes while applying tension using a transport roll with a diameter of 70 mm or more. The applied tension is, for example, 5 to 50 N / mm in the rolling direction of the steel foil. 2The conveying speed during the heat treatment is 0.1 to 30.0 m / min. The steel foil for current collector after the heat treatment is visually checked for the presence or absence of buckling. In this specification, buckling refers to unevenness formed on the surface of the steel foil for current collector. When no buckling is confirmed in the steel foil for current collector as a result of visual inspection, it is determined that buckling is unlikely to occur.
[0069] [Bend] The steel foil for a current collector according to the present embodiment is resistant to buckling or bending when subjected to a heat treatment at a high temperature sufficient to crystallize the active material after the active material layer is formed. In the present embodiment, the resistance to bending can be evaluated by the following method.
[0070] A test piece is prepared from the steel foil for current collector according to this embodiment. The size of the test piece is 30 mm in the rolling direction of the ferritic stainless steel foil and 150 mm in the width direction. An active material layer is formed on the surface of the test piece using lithium cobalt oxide (LiCoO2) as an active material, and heat treated at 700°C for 20 minutes. One end of the test piece in the longitudinal direction after the heat treatment is fixed to the upper end of a right-angle plate, and the test piece is placed so as to be in contact with the right-angle plate. The distance between the other end (lower end) of the test piece in the longitudinal direction and the right-angle plate is measured with a ruler and defined as the "warping amount" of the test piece. In this embodiment, if the warping amount is 5 mm or less, it is determined that bending is unlikely to occur. Furthermore, in this embodiment, if the warping amount is 3 mm or less, it is determined that bending is very unlikely to occur.
[0071] [Cycle characteristics] The steel foil for a current collector according to this embodiment can provide an all-solid-state secondary battery having excellent cycle characteristics. In this embodiment, whether the all-solid-state secondary battery has excellent cycle characteristics can be evaluated by the following method.
[0072] First, a simulated product simulating an all-solid-state secondary battery is produced. Specifically, a test piece is cut out from the steel foil for a current collector according to this embodiment. A positive electrode conductor layer is formed on the cut out test piece by sputtering. The sputtering is performed, for example, using a DC (Direct Current) sputtering device, using Pt as a target material, without heating, in an Ar atmosphere, so that the film thickness becomes 1.0 μm.
[0073] A positive electrode active material layer is formed on the positive electrode conductive layer by sputtering, for example, using an RF (Radio Frequency) sputtering device so that the thickness of the lithium cobalt oxide (LiCoO2) layer is 0.45 μm.
[0074] The test piece on which the positive electrode active material layer is formed is subjected to an annealing treatment. The annealing treatment is performed at a temperature of 600°C. A solid electrolyte layer is formed by sputtering on the positive electrode active material layer of the test piece on which the annealing treatment has been performed. The sputtering is performed, for example, using an RF sputtering device so that the film thickness of lithium oxynitride phosphate (Li3PON4) becomes 1.4 μm.
[0075] On the formed solid electrolyte layer, a negative electrode current collector layer is formed by sputtering. Sputtering is performed, for example, using a DC sputtering device so that the thickness of the copper (Cu) film is 1.0 μm. On the formed negative electrode current collector layer, a protective layer is formed by sputtering. Sputtering is performed, for example, using an RF sputtering device so that the thickness of the silicon dioxide (SiO2) film is 0.05 to 1.0 μm. In this embodiment, a mock-up simulating an all-solid-state secondary battery is fabricated as described above.
[0076] The cycle characteristics are evaluated using the prepared simulant. Specifically, the simulant is charged at a constant current of 0.1C at rate C from the rest potential to 4.2V. Then, a constant voltage charge of 4.2V is performed for 20 hours. The simulant charged in the above manner is discharged at a constant current of 0.1C at rate C until the voltage reaches 3.0V. The discharge capacity by this constant current discharge is defined as the initial discharge capacity Qd1 (mAh).
[0077] Here, one cycle is defined as a constant current charge of 0.1C until the voltage reaches 4.2V, a constant voltage charge at 4.2V for 20 hours, and a constant current discharge of 0.1C until the voltage reaches 3.0V. The simulated product for which the initial discharge capacity Qd1 (mAh) was measured is subjected to nine more cycles of charge and discharge. When the initial discharge capacity Qd1 (mAh) is defined as the first cycle, the discharge capacity by constant current discharge in the tenth cycle is defined as the tenth cycle discharge capacity Qd10 (mAh). In this embodiment, the capacity retention rate is defined by the following formula (1). Capacity maintenance rate (%)=100×Qd10 / Qd1 (1)
[0078] [Manufacturing method of steel foil for current collectors] An example of a method for manufacturing a steel foil for a current collector according to the present embodiment will be described. The manufacturing method described below is one example for manufacturing a steel foil for a current collector according to the present embodiment, and the manufacturing method of the steel foil for a current collector according to the present embodiment may be a manufacturing method other than the manufacturing method described below. However, the manufacturing method described below is a preferred example of a method for manufacturing a steel foil for a current collector according to the present embodiment. The manufacturing method of a steel foil for a current collector according to the present embodiment includes an intermediate steel material preparation step, a final cold rolling step, and a heat treatment step.
[0079] [Intermediate steel preparation process] In the intermediate steel material preparation step, an intermediate steel material having the same chemical composition as the ferritic stainless steel foil, which is the base material of the steel foil for the current collector, is prepared. That is, the intermediate steel material is an intermediate product for manufacturing the ferritic stainless steel foil according to this embodiment, and means a steel plate having a thickness of several tens to several hundreds of μm. The intermediate steel material is, for example, a cold-rolled coil obtained by cold rolling a hot-rolled coil. The intermediate steel material may be prepared by manufacturing, or may be prepared by purchasing from a third party. That is, the step of preparing the intermediate steel material is not particularly limited.
[0080] When intermediate steel materials are produced, for example, they are produced by the following method. Molten steel having a desired chemical composition is produced. A cast piece (slab, bloom, or billet) is produced by a continuous casting method using the molten steel. A steel ingot (ingot) may be produced by an ingot casting method using the molten steel. If necessary, the slab, bloom, or ingot may be rolled to produce a billet.
[0081] The produced cast or steel ingot (slab, bloom, billet, or ingot) is subjected to hot working and cold rolling to produce a steel plate having a thickness of several tens to several hundreds of μm. The method of hot working is not particularly limited, and any well-known method may be used. The hot working is, for example, hot rolling. When producing an intermediate steel material by hot rolling, it can be produced, for example, by the following method.
[0082] After the produced slab or steel ingot is heated, rough rolling and finish rolling are carried out. At this time, the conditions of the hot rolling are not particularly limited, and well-known conditions may be appropriately set. The hot-rolled intermediate steel material may be repeatedly subjected to cold rolling and annealing treatment as necessary. The hot-rolled intermediate steel material may further be subjected to skin pass rolling as necessary. The hot-rolled and / or cold-rolled intermediate steel material is further subjected to annealing treatment. Through the above steps, the intermediate steel material according to this embodiment is prepared.
[0083] [Final cold rolling process] In the final cold rolling process, cold rolling is performed on the intermediate steel material prepared in the intermediate steel material preparation process. In the present embodiment, the cold rolling can be performed using a known device, and is not particularly limited. For example, a continuous rolling mill equipped with multiple cold rolling stands may be used.
[0084] In the final cold rolling step according to this embodiment, the surface roughness of the rolling roll surface is preferably 0.03 to 0.30 μm in terms of arithmetic mean roughness Ra. If the surface roughness of the rolling roll surface is too small, the surface roughness of the produced ferritic stainless steel foil may be too small. On the other hand, if the surface roughness of the rolling roll surface is too large, the surface roughness of the produced ferritic stainless steel foil may be too large. Therefore, in the final cold rolling step according to this embodiment, the arithmetic mean roughness Ra of the rolling roll surface is preferably 0.03 to 0.30 μm.
[0085] In the final cold rolling step according to the present embodiment, the reduction ratio R is preferably set to 35 to 98%. Here, the reduction ratio R in the final cold rolling step means the reduction rate (%) of the thickness of the intermediate steel material from before the final cold rolling step to after the final cold rolling step. That is, the reduction ratio R in the final cold rolling step is defined by the following formula (A). R(%)=[{(thickness of intermediate steel before final cold rolling process)-(thickness of intermediate steel after final cold rolling process)}] / (thickness of intermediate steel before final cold rolling process)×100 (A)
[0086] If the reduction ratio R in the final cold rolling step is too low, the amount of strain energy introduced into the intermediate steel material by cold rolling decreases. In this case, the heat treatment temperature required to release the strain in the heat treatment step described later becomes high. In other words, if the reduction ratio R in the final cold rolling step is too low and the heat treatment temperature in the heat treatment step described later is too low, the half-width Fw of the {110} plane may become too high in the ferritic stainless steel foil of the current collector steel foil produced. As a result, buckling is likely to occur in the current collector steel foil due to heat treatment at a high temperature that crystallizes the active material.
[0087] In the final cold rolling step, the surface of the foil strip is transferred to the surface shape of the rolling roll as the roll is reduced, so that the unevenness formed on the surface of the intermediate steel material changes. Therefore, if the reduction rate in the final cold rolling step is too low, the surface roughness of the foil strip surface cannot be controlled, and the unevenness formed on the surface of the intermediate steel material remains, so that the surface roughness may become too large. In this case, the Ra1 and / or Ra2 of the surface of the manufactured ferritic stainless steel foil may exceed 0.30 μm. In this case, the cycle characteristics of the all-solid-state secondary battery manufactured using the steel foil for current collector having the ferritic stainless steel foil as a base material are deteriorated.
[0088] On the other hand, if the reduction ratio R in the final cold rolling process is too high, the amount of strain introduced into the intermediate steel by cold rolling becomes too high. In this case, there is a concern that fracture may occur at the end of the intermediate steel. Therefore, in the final cold rolling process according to this embodiment, the preferable reduction ratio R is 35 to 98%. A more preferable lower limit of the reduction ratio R in the final cold rolling process is 40%, and more preferably 45%. A more preferable upper limit of the reduction ratio R in the final cold rolling process is 96%, and more preferably 95%.
[0089] In the final cold rolling step according to the present embodiment, a step other than cold rolling may also be performed. For example, slitting may be performed on the intermediate steel material to process the intermediate steel material into an arbitrary size. In this case, in the final cold rolling step, slitting may be performed after cold rolling, cold rolling may be performed after slitting, or slitting may be performed between cold rolling and cold rolling.
[0090] [Heat treatment process] In the heat treatment step, heat treatment is performed on the intermediate steel material after the final cold rolling step. In this embodiment, the heat treatment can be performed by passing the steel material through a known heat treatment furnace. In this embodiment, the atmosphere in the heat treatment step is preferably an inert gas atmosphere such as nitrogen, or a reducing gas atmosphere such as hydrogen.
[0091] The preferred heat treatment temperature in the heat treatment step is 350 to 700°C. If the heat treatment temperature is too low, the intermediate steel material cannot be sufficiently released from the strain. As a result, the half-value width Fw of the {110} plane may be too high in the ferritic stainless steel foil of the current collector steel foil produced. In this case, the heat treatment at a high temperature that crystallizes the active material may easily cause buckling in the current collector steel foil. On the other hand, if the heat treatment temperature is too high, the intermediate steel material is released too much strain. As a result, the half-value width Fw of the {110} plane may be too low in the ferritic stainless steel foil of the current collector steel foil produced. In this case, the heat treatment at a high temperature that crystallizes the active material may easily cause bending in the current collector steel foil.
[0092] Therefore, in this embodiment, the heat treatment temperature in the heat treatment step is preferably 350 to 700°C. A more preferable lower limit of the heat treatment temperature is 400°C. A more preferable upper limit of the heat treatment temperature is 650°C. A more preferable heat treatment temperature is 350 to 550°C. In this case, the half-width Fw of the {110} plane in the ferritic stainless steel foil of the produced current collector steel foil is stably 0.45 to 0.52°, and bending of the current collector steel foil is further easily suppressed by heat treatment at a high temperature sufficient to crystallize the active material.
[0093] The preferred heat treatment time in the heat treatment step is 1 to 400 seconds. If the heat treatment time is too short, the intermediate steel material cannot be sufficiently released from the strain. As a result, the half-value width Fw of the {110} plane may be too high in the ferritic stainless steel foil of the current collector steel foil produced. In this case, the heat treatment at a high temperature to crystallize the active material may easily cause buckling in the current collector steel foil. On the other hand, if the heat treatment time is too long, the intermediate steel material may be released too much from the strain. As a result, the half-value width Fw of the {110} plane may be too low in the ferritic stainless steel foil of the current collector steel foil produced. In this case, the heat treatment at a high temperature to crystallize the active material may easily cause bending in the current collector steel foil.
[0094] Therefore, in this embodiment, the heat treatment time in the heat treatment step is preferably 1 to 400 seconds. A more preferable lower limit of the heat treatment time is 2 seconds, and more preferably 3 seconds. A more preferable upper limit of the heat treatment time is 300 seconds, and more preferably 250 seconds. In this specification, the heat treatment temperature in the heat treatment step means the temperature (°C) of a heat treatment furnace for carrying out the heat treatment. In this specification, the heat treatment time in the heat treatment step means the time (seconds) required for an intermediate steel material to pass through a heat treatment furnace for carrying out an annealing treatment.
[0095] The above manufacturing steps allow the current collector steel foil according to this embodiment having the above-mentioned configuration to be manufactured. Note that the above manufacturing steps are one example of the method for manufacturing the current collector steel foil according to this embodiment, and the method for manufacturing the current collector steel foil according to this embodiment is not limited to the above manufacturing method. In addition, the method for manufacturing the current collector steel foil according to this embodiment may further include any of the steps described below. The steps described below are optional and may not be performed.
[0096] [Tension annealing process] The method for producing a steel foil for a current collector according to the present embodiment may further include a tension annealing step after the final cold rolling step and before the heat treatment step. Tension annealing means performing an annealing treatment while applying tension. The intermediate steel material that has been subjected to tension annealing can maintain the flatness of the intermediate steel material by the tension.
[0097] When the tension annealing step is performed, the annealing temperature is preferably 350 to 450°C. If the annealing temperature is too low, the effect of tension annealing may not be sufficiently obtained. On the other hand, if the annealing temperature is too high, the introduced dislocation density in the microstructure of the intermediate steel material may be too low. As a result, in the manufactured ferritic stainless steel foil, the half-width Fw of the peak of the {110} plane in the X-ray diffraction profile by CoKα rays may not be sufficiently increased. Therefore, in this embodiment, when the tension annealing step is performed, the annealing temperature is preferably 350 to 450°C.
[0098] When the tension annealing step is performed, the annealing time is not particularly limited. The annealing time is, for example, 1 to 10 seconds. In this specification, the "annealing temperature" of tension annealing means the temperature (°C) of a heat treatment furnace for performing the annealing treatment. In this specification, the "annealing time" of tension annealing means the time (seconds) required for the intermediate steel material to pass through a heat treatment furnace for performing the annealing treatment. In addition, when the tension annealing step is performed, the tension applied to the intermediate steel material is not particularly limited.
[0099] [Resin film formation process] The method for producing a steel foil for a current collector according to the present embodiment may further include a resin coating step after the final cold rolling step and before the heat treatment step. As described above, by forming a resin coating, the insulation property, heat resistance, and flatness of the steel foil for a current collector can be improved.
[0100] When the resin coating forming step is carried out, a resin coating is formed on the surface of the intermediate steel material cold rolled by the final cold rolling step. As described above, in this embodiment, the resin coating is not particularly limited, but is, for example, an inorganic-organic hybrid resin coating. The method for forming the resin coating is not particularly limited, and may be a well-known method. For example, the resin coating may be formed by applying a composition containing the components of the resin coating and drying it.
[0101] If necessary, a heat treatment may be carried out to harden the resin coating. In this case, it is preferable to harden the resin coating in the heat treatment step described above. When the resin coating is hardened by heat treatment in the heat treatment step, the resin coating can be hardened while appropriately controlling the distortion of the ferritic stainless steel foil by the heat treatment step. In this case, productivity can be increased.
[0102] [Manufacturing method of all-solid-state secondary battery] The method for producing the all-solid-state secondary battery is not particularly limited, and a well-known method can be used. As described above, the all-solid-state secondary battery according to the present embodiment can be produced by laminating a thin film of an active material layer and a thin film of a solid electrolyte layer on or above the steel foil for a current collector according to the present embodiment. Here, the method for laminating the thin film uses, for example, a vacuum film formation method represented by a sputtering method or an electron beam deposition method.
[0103] When the sputtering method is used, the sputtering method is not particularly limited, and any known sputtering method can be appropriately selected and used. For example, the sputtering method may be a DC sputtering method, a RF sputtering method, or an ion beam sputtering method.
[0104] The steel foil for a current collector according to the present embodiment will be described in more detail below with reference to examples. Note that the examples described below are examples for confirming the effects of the steel foil for a current collector according to the present embodiment, and do not limit the present invention. EXAMPLES
[0105] Intermediate steel materials were prepared for each test number with a thickness (μm) shown in Table 1. All intermediate steel materials for each test number were intermediate steel materials made of ferritic stainless steel equivalent to SUS444 specified in JIS G 4305 (2012). All intermediate steel materials were annealed at 840 to 950°C for 3 to 30 seconds.
[0106] [Table 1]
[0107] Cold rolling was performed on the intermediate steel material of each test number using a rolling roll. The rolling rolls used are shown in Table 1. In Table 1, a rolling roll having an arithmetic mean roughness Ra of the roll surface of less than 0.03 μm is indicated as "A". In Table 1, a rolling roll having an arithmetic mean roughness Ra of the roll surface of less than 0.03 to 0.10 μm is indicated as "B". In Table 1, a rolling roll having an arithmetic mean roughness Ra of the roll surface of less than 0.10 to 0.30 μm is indicated as "C". In Table 1, a rolling roll having an arithmetic mean roughness Ra of the roll surface of less than 0.30 to 0.60 μm is indicated as "D". The reduction ratio (%) in the cold rolling was as shown in Table 1.
[0108] In this way, a substrate (ferritic stainless steel foil) having a substrate thickness (μm) as shown in Table 1 was obtained. The annealing described in the "annealing treatment" column was performed on some of the substrates having test numbers among the obtained substrates. Tension annealing was performed on the substrates having test numbers 6 to 8 (represented as "TA (Tension Annealing)" in Table 1). In this example, as tension annealing, a heat treatment was performed at 400°C for 4 seconds. Bright annealing was performed on the substrates having test numbers 16 and 17 (represented as "BA (Bright Annealing)" in Table 1). Bright annealing means annealing performed under conditions in which the surface of the ferritic stainless steel foil is not nitrided. In this example, as bright annealing, a heat treatment was performed at 950°C for 4 seconds with a nitrogen concentration in the atmosphere of 0.1% or less.
[0109] A composition for forming a siloxane-based resin coating was applied to one side of the obtained substrate having each test number. The substrate with the composition applied to one side was subjected to a heat treatment at a heat treatment temperature shown in Table 1 for 20 to 300 seconds. Note that "-" in the "Heat treatment temperature (°C)" column in Table 1 means that no heat treatment was performed. Through the above steps, a steel foil for a current collector according to this embodiment was manufactured.
[0110] [Evaluation test] For the steel foil for current collector having each test number, a half-width Fw measurement test, a surface roughness measurement test, a buckling evaluation test, a bending evaluation test, and a cycle characteristic evaluation test were performed.
[0111] [Half-width Fw measurement test] A half-width Fw measurement test was carried out on the current collector steel foil of each test number to obtain the half-width Fw of the {110} plane. Specifically, a test piece was prepared from the current collector steel foil of each test number, and an X-ray diffraction profile was obtained by the oblique incidence X-ray diffraction method (GIXD). Of the test pieces, a surface on which no resin coating was formed was specified and used as the observation surface. In the oblique incidence X-ray diffraction method (GIXD), the radiation source was CoKα radiation, the tube voltage was 40 kV, and the tube current was 135 mA. In addition, the X-ray beam was collimated by a mirror. The solar slit was set to 5° on the entrance side and 2.5° on the diffraction side. 12 conditions were set for the incidence angle in the range of 1 to 25° so that the measurement depth from the observation surface of the test piece was 12 points in the range of 0.19 to 4.60 μm.
[0112] At each measurement point, the peak of the {110} plane was identified from the X-ray profile and the half-width was calculated. The arithmetic mean value of the 12 half-widths obtained was defined as the half-width Fw of the {110} plane. For the measurement depth, the X-ray penetration depth t that satisfies μt=1, where μ is the linear absorption coefficient, was calculated and used after converting it into the depth from the observation surface of the test piece. The mass absorption coefficient used was 19.11Cr-1.77Mo-78.38Fe (mass%). Furthermore, the density of the ferritic stainless steel foil was 7.75g / cm 3 The half-value width Fw(°) of the {110} plane obtained for the current collector steel foil of each test number is shown in Table 1.
[0113] [Surface roughness measurement test] A surface roughness measurement test was carried out on the current collector steel foil of each test number to determine the arithmetic mean roughness Ra1 and Ra2. Specifically, a test piece was prepared from the current collector steel foil of each test number and fixed to a glass substrate. The surface of the test piece on which the resin film was formed was specified as the glass substrate. Three arbitrary positions were specified from the test piece fixed to the glass substrate and used as measurement points. In this example, the arbitrary direction (direction 1) was set to a direction parallel to the rolling direction of the ferritic stainless steel foil. The direction perpendicular to direction 1 (direction 2) was set to a direction parallel to the width direction of the ferritic stainless steel foil.
[0114] At each measurement point, the arithmetic mean roughness (μm) was measured in each of directions 1 and 2 in accordance with the method specified in JIS B 0601 (2001). The roughness meter used in measuring the arithmetic mean roughness was a contact type surface roughness measuring instrument, Surftest SJ-301 (product name), manufactured by Mitutoyo Corporation. Furthermore, the conditions for calculating the roughness curve were as follows: Measuring force: 0.75mN Stylus tip shape (when using a contact type roughness gauge): 2μmR60° Cutoff value λc: 0.25 mm Cutoff value λs: 2.5μm Number of sections: 5 Measurement speed: 0.25mm / sec Reference length: 0.25 mm Evaluation length: 1.25mm
[0115] The obtained arithmetic mean roughness Ra1 (μm) in direction 1 and the arithmetic mean roughness Ra2 (μm) in direction 2 are shown in Table 1.
[0116] [Buckling evaluation test] A buckling evaluation test was carried out on the current collector steel foil of each test number to evaluate the occurrence of buckling. Specifically, an active material layer was formed by vapor deposition on the surface of the current collector steel foil of each test number on which the siloxane-based resin coating was not formed. In this example, lithium cobalt oxide (LiCoO2) was used as the active material. Note that, for each test number, the size of the current collector steel foil was 300 to 600 mm in the width direction of the steel foil. The current collector steel foil coated with the active material was heat-treated at 700°C for 20 minutes while applying tension using a transport roll with a diameter of 70 mm. Note that the applied tension was 5 to 50 N / mm in the rolling direction of the steel foil. 2 The conveying speed during the heat treatment was set to 0.1 to 30.0 m / min.
[0117] The current collector steel foils of each test number after the heat treatment were visually inspected for the presence or absence of buckling. More specifically, when no streaky irregularities extending in the rolling direction of the steel foil were observed in the current collector steel foils of each test number, it was determined that buckling was unlikely to occur (represented as "E (Excellent)" in Table 1). On the other hand, when streaky irregularities extending in the rolling direction of the steel foil were formed at intervals of several mm to several tens of mm in the current collector steel foils of each test number, it was determined that buckling was likely to occur (represented as "NA (Not Acceptable)" in Table 1).
[0118] [Flexibility evaluation test] A bending evaluation test was carried out on the current collector steel foil of each test number to evaluate whether bending occurred or not. In this embodiment, the bending evaluation test was carried out on the current collector steel foil of the test number that was determined to be unlikely to buckle in the buckling evaluation test. Specifically, a test piece for bending evaluation was prepared from the current collector steel foil of each test number. The test piece was 30 mm in the rolling direction of the steel foil and 150 mm in the width direction. An active material layer was formed on the surface of the test piece by vapor deposition. In this embodiment, lithium cobalt oxide (LiCoO2) was used as the active material. The test piece on which the active material layer was formed was heat treated at 700°C for 20 minutes. One end of the longitudinal direction of the heat-treated test piece was fixed to the upper end of a right-angle plate, and the test piece was placed so as to be in contact with the right-angle plate.
[0119] The distance between the other end (lower end) of the test piece in the longitudinal direction and the right-angle surface plate was measured with a ruler and defined as the "warping amount" of the test piece. For the steel foil for current collector with each test number, if the warping amount was 5 mm or less, it was judged that bending was unlikely to occur (indicated as "G (Good)" in Table 1). Furthermore, for the steel foil for current collector with each test number, if the warping amount was 3 mm or less, it was judged that bending was very unlikely to occur (indicated as "E (Excellent)" in Table 1). On the other hand, for the steel foil for current collector with each test number, if the warping amount was more than 5 mm, it was judged that bending was likely to occur (indicated as "NA (Not Acceptable)" in Table 1).
[0120] [Cycle characteristic evaluation test] A cycle characteristic evaluation test was performed on the current collector steel foil of each test number to evaluate the cycle characteristics. In this example, the cycle characteristic evaluation test was performed on the current collector steel foil of the test number that was judged to be unlikely to buckle in the buckling evaluation test and to be unlikely to bend in the bending evaluation test. Specifically, a simulated all-solid-state secondary battery for cycle characteristic evaluation was produced from the current collector steel foil of each test number.
[0121] The simulants were manufactured by the following method. First, a steel foil was cut out to prepare a test piece. A positive electrode conductor layer was formed on the surface of the test piece by sputtering using a DC sputtering device. At this time, the target material was Pt, and sputtering was performed without heating and in an Ar atmosphere so that the film thickness was 1.0 μm. A positive electrode active material layer was formed on the formed positive electrode conductor layer of the test piece by sputtering using an RF sputtering device. The active material of the positive electrode active material layer was lithium cobalt oxide (LiCoO2), and the film thickness of the positive electrode active material layer was 0.45 μm. Furthermore, the test piece on which the positive electrode active material layer was formed was subjected to an annealing treatment in which the test piece was heat-treated at 600°C.
[0122] Of the test pieces that had been annealed, a solid electrolyte layer was formed on the positive electrode active material layer by sputtering using an RF sputtering device. The electrolyte of the solid electrolyte layer was lithium oxynitride phosphate (Li3PON4), and the thickness of the solid electrolyte layer was 1.4 μm. Of the test pieces, a negative electrode current collector layer was formed on the formed solid electrolyte layer by sputtering using a DC sputtering device. The conductive material of the negative electrode current collector layer was copper (Cu), and the thickness of the negative electrode current collector layer was 1.0 μm. Of the test pieces, a protective layer was formed on the formed negative electrode current collector layer by sputtering using an RF sputtering device. The protective layer was mainly composed of silicon dioxide (SiO2), and the thickness of the protective layer was 0.05 to 1.0 μm. Using the simulants prepared as described above, the cycle characteristics of each test number were evaluated.
[0123] Specifically, the simulated samples of each test number were charged at a constant current of 0.1C at a rate of C from the rest potential to 4.2V. Then, a constant voltage charge of 4.2V was performed for 20 hours. The simulated samples charged in the above manner were discharged at a constant current of 0.1C at a rate of C until the potential reached 3.0V. In this embodiment, the discharge capacity by this constant current discharge was defined as the initial discharge capacity Qd1 (mAh).
[0124] Here, in this embodiment, a constant current charge of 0.1C until the battery voltage reaches 4.2V, a constant voltage charge at 4.2V for 20 hours, and a constant current discharge of 0.1C until the battery voltage reaches 3.0V were defined as one cycle. Nine cycles of charge and discharge were further performed on the simulated sample for which the initial discharge capacity Qd1 (mAh) was measured. In this embodiment, when the initial discharge capacity Qd1 (mAh) was defined as the first cycle, the discharge capacity by the constant current discharge in the 10th cycle was defined as the discharge capacity Qd10 (mAh) in the 10th cycle. In this embodiment, the capacity retention rate was further defined by the following formula (1). Capacity maintenance rate (%)=100×Qd10 / Qd1 (1)
[0125] In this example, the capacity retention rate (%) of each test number was evaluated using a relative value. Specifically, the capacity retention rate (%) of test number 14 was used as a reference value, and the capacity retention rate (%) of each test number was evaluated relatively. When the capacity retention rate of the current collector steel foil of each test number was greater than the reference value, it was determined that it had excellent cycle characteristics (represented as "E (Excellent)" in Table 1). On the other hand, when the capacity retention rate of the current collector steel foil of each test number was about the same as the reference value, it was determined that it did not have excellent cycle characteristics (represented as "NA1 (Not Acceptable 1)" in Table 1). Furthermore, when the capacity retention rate of the current collector steel foil of each test number was smaller than the reference value, it was also determined that it did not have excellent cycle characteristics (represented as "NA2 (Not Acceptable 2)" in Table 1).
[0126] [Evaluation Results] The current collector steel foils of test numbers 1 to 9 had a half-width Fw of the {110} plane of the ferritic stainless steel foil of 0.40 to 0.52°. Furthermore, the arithmetic mean roughness Ra1 in the rolling direction (direction 1) and the arithmetic mean roughness Ra2 in the width direction (direction 2) of these current collector steel foils both satisfied 0.03 to 0.30 μm. As a result, in the buckling evaluation test, it was determined that buckling was unlikely to occur. As a result, in the bending evaluation test, the warpage was 5 mm or less, and it was determined that bending was unlikely to occur. As a result, in the cycle characteristic evaluation test, the capacity retention rate was greater than the reference value, and it was determined that the current collector steel foils had excellent cycle characteristics. That is, after forming the active material layer, these current collector steel foils were unlikely to buckle or bend when heat-treated at a high temperature to crystallize the active material, and further, when used in an all-solid-state secondary battery, they had excellent cycle characteristics.
[0127] The current collector steel foils of test numbers 1 to 8 further had a half-value width Fw of the {110} plane of the ferritic stainless steel foil of 0.45 to 0.52°. As a result, in the bending evaluation test, the amount of warping was 3 mm or less, and it was determined that bending was very unlikely to occur.
[0128] On the other hand, the steel foils for current collectors of test numbers 10 and 11 had too small surface roughness of the rolling roll. As a result, the arithmetic mean roughness Ra1 of these steel foils for current collectors in direction 1 was less than 0.03 μm. As a result, in the cycle performance evaluation test, the capacity retention rate was approximately the same as the reference value, and it was determined that they did not have excellent cycle performance.
[0129] The current collector steel foils of test numbers 12 and 13 had too large surface roughness of the rolling roll. As a result, the arithmetic mean roughness Ra2 of these current collector steel foils in direction 2 exceeded 0.30 μm. As a result, in the cycle performance evaluation test, the capacity retention rate was smaller than the reference value, and it was determined that the current collector steel foils did not have excellent cycle performance.
[0130] The current collector steel foil of test number 14 had a rolling roll with a too small surface roughness. As a result, the arithmetic mean roughness Ra1 in direction 1 of these current collector steel foils was less than 0.03 μm, and the arithmetic mean roughness Ra2 in direction 2 of these current collector steel foils was less than 0.03 μm. In the cycle performance evaluation test, this current collector steel foil was used as the reference value, and it was determined that a capacity retention rate equivalent to the reference value did not have excellent cycle performance.
[0131] The heat treatment temperature in the heat treatment step of the current collector steel foil of test number 15 was too high. As a result, the half-value width Fw of the {110} plane of the ferritic stainless steel foil of this current collector steel foil was less than 0.40°. As a result, the amount of warping exceeded 5 mm in the bending evaluation test, and it was determined that bending was likely to occur.
[0132] The current collector steel foil of test number 16 was bright annealed before the heat treatment process. Furthermore, no heat treatment process was performed. As a result, the half-value width Fw of the {110} plane of the ferritic stainless steel foil of this current collector steel foil was less than 0.40°. As a result, in the bending evaluation test, the amount of warping exceeded 5 mm, and it was determined that bending was likely to occur.
[0133] The current collector steel foil of test number 17 was bright annealed before the heat treatment process. As a result, the half-value width Fw of the {110} plane of the ferritic stainless steel foil of this current collector steel foil was less than 0.40°. As a result, the amount of warping exceeded 5 mm in the bending evaluation test, and it was determined that bending was likely to occur.
[0134] The current collector steel foils of test numbers 18 and 19 were not subjected to a heat treatment process. As a result, the half-value width Fw of the {110} plane of the ferritic stainless steel foil exceeded 0.52° in these current collector steel foils. As a result, it was determined that buckling was likely to occur in the buckling evaluation test.
[0135] The heat treatment temperature in the heat treatment step of the current collector steel foil of test number 20 was too low. As a result, the half-value width Fw of the {110} plane of the ferritic stainless steel foil of this current collector steel foil exceeded 0.52°. As a result, it was determined that buckling was likely to occur in the buckling evaluation test.
[0136] The surface roughness of the rolling roll of the current collector steel foil of test number 21 was too small. Furthermore, the reduction ratio in the final cold rolling process was too low. As a result, the half-value width Fw of the {110} plane of the ferritic stainless steel foil of this current collector steel foil exceeded 0.52°. As a result, it was judged that buckling was likely to occur in the buckling evaluation test.
[0137] The embodiments of the present disclosure have been described above. However, the above-described embodiments are merely examples for implementing the present disclosure. Therefore, the present disclosure is not limited to the above-described embodiments, and can be implemented by appropriately modifying the above-described embodiments without departing from the spirit of the present disclosure.
Claims
1. A steel foil for a collector used in an electrode of a secondary battery, comprising: The device is provided with ferritic stainless steel foil, In the ferritic stainless steel foil, in an X-ray diffraction profile using CoKα radiation, the half-value width Fw of the peak of the {110} plane is 0.40 to 0.52°, On the surface of the ferritic stainless steel foil, The arithmetic mean roughness in any direction is defined as Ra1, When the arithmetic average roughness in a direction perpendicular to the arbitrary direction is defined as Ra2, The Ra1 and Ra2 are both 0.03 to 0.30 μm; Steel foil for current collectors.
2. The steel foil for a current collector according to claim 1, The thickness of the ferritic stainless steel foil is 5 to 60 μm. Steel foil for current collectors.
3. The steel foil for a current collector according to claim 1, A resin coating is formed on the surface of the ferritic stainless steel foil. Steel foil for current collectors.
4. The steel foil for a current collector according to claim 2, A resin coating is formed on the surface of the ferritic stainless steel foil. Steel foil for current collectors.
5. The steel foil for a current collector according to any one of claims 1 to 4, An active material layer; A solid electrolyte layer; A current collector layer. All-solid-state secondary battery.
Citation Information
Patent Citations
Lithium battery
JP2003178753A
Non-aqueous electrolyte battery
JP2003178766A
HIGH Cr STEEL SHEET FOR ENERGIZING COMPONENT HAVING IMPROVED ELECTRICAL CONDUCTIVITY AND SPRING PROPERTY
JP2005126808A
Method for heat-treating soft magnetic metal powder
JP2007138197A
Steel foil for solar cell substrate, method for manufacturing the same, solar cell substrate, solar cell, and method for manufacturing solar cell
JP2012138571A